POLA ASUH ORANG TUA MILENIAL DALAM MENINGKATKAN PERKEMBANGAN MORAL ANAK USIA DINI - Rina Fitria; Deni Widjayatri (STPI Bina Insan Mulia Yogyakarta, 2022)
This study aims to find out and understand the importance of parenting in the current millennial era in improving the moral development of early childhood. This research uses a qualitative approach with a literature study research method. The results and discussion explain that the parenting pattern of millennial parents currently plays an important role in the moral development of children, including through the application of democratic parenting, children are able to manage their emotions and be independent. Not only that, the current parenting pattern for millennial parents can be done by providing parenting in the form of habituation and example or providing good examples (figures) for children, so that children are able to imitate the habits that parents apply to shape good behavior, character in accordance with applicable norms and have a responsible and independent nature. Parents are also able to instill religious values ​​in their children from an early age.